Novel Li4Ti5O12/Si/c-PAN composite anode for Lithium-ion batteries - Nyssanbayev, Anuar; Sanbayeva, Ayana; Nurpeissova, Arailym; Rachid Babaa, Moulay; Bakenov, Zhumabay (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
This work investigates a combined LTO/Si composite anode in a LIB with excellent electrochemical performance. The LTO/Si system is dispersed in cyclized polyacrylonitrile (c-PAN) polymer matrix, which is widely used as an active conductive material in order to improve electrical conductivity and binding abilities.....
Keywords: lithium titanium oxide; silicon